Preparation and properties of expandable epoxy foam prepreg for sandwich composites prepared via thermal expansion molding process. Issue 7 (30th November 2022) - Min, Wei; Qi, Liangliang; Zhao, Xinxing; Xiao, Jie; Wan, YuJia; Yu, Muhuo; Sun, Zeyu
Abstract: Thermal expansion molding process (TEMP) is a new technology for integrated molding sandwich composites. However, the development of high‐performance expandable foam prepreg limits the scale applications of this technology. In this study, epoxy foam prepreg (M‐1) with expandable function was used to prepare foams with different expansion ratios via restricted foaming. Three suitable expansion ratios were determined to prepare foam sandwich composites by analyzing the density, bubble sizes, compressive strength, and expansion pressures of expandable foam. The maximum expansion pressure produced by four, six, and eight times of foam expansion were 251, 160, and 115 kPa, respectively. Tensile test and digital imaging computer technology confirmed that with the increase of foam expansion ratio, the strength decreased, but the plastic deformation ability increased. Failure modes such as foam matrix fracture, glass fiber mat fracture, and mutual‐slipping between the foam matrix and glass fiber mat occur during the stretching process. Finally, the PMI/M‐1 foam hybrid sandwich composites with three structures were prepared via the TEMP technology, which verified the feasibility of this technology in forming sandwich composites. Abstract : A kind of epoxy foam prepreg with thermal expansion function was prepared. The microstructure, mechanical properties, and expansion pressure of the foam at different expansion ratio were determined by experiments. In particular, this prepreg is epoxy foam coated on glass fiber mat, and the tensile failure mode is studied by tensile test and digital imaging computer technique. Furthermore, three kinds of hybrid foam sandwich plates were prepared to study the bending behavior of short beams.